Peran Doktrin Gereja Dalam Kehidupan Umat Kristen - Selamita; Putri, Meisylina; Dwiyanti, Tika; Sarmauli, Sarmauli (Paramathetes : Jurnal Teologi dan Pendidikan Kristiani, 2024)
Abstract. Throughout its history, the Church has faced various internal and external problems, including divisions (schism), heresy, and social changes that require the Church to continue to adapt to the dynamics of an ever-changing world. Modern challenges such as secularism, moral relativism, and developments in technology and information also affect the lives of Christians. This research will comprehensively review various dimensions of Ecclesiology doctrine, starting from the basic understanding of the Church according to the Bible, the role of the Church in the Christian tradition, as well as the historical development of the concept of the Church. Apart from that, it will also be discussed how the Church plays a role in the lives of believers through sacraments, proclamation of the Gospel, and social action. The method used in this research is descriptive literature study using various sources such as books, journals, articles related to church doctrine. The research findings show that church doctrine has an important role in the lives of Christians. This is based on the teachings contained in church doctrine being the basis of Christian faith. Abstrak. Sepanjang sejarahnya, Gereja telah menghadapi berbagai masalah internal maupun eksternal, termasuk perpecahan (skisma), ajaran sesat (heresy), dan perubahan sosial yang mengharuskan Gereja untuk terus menyesuaikan diri dengan dinamika dunia yang terus berubah. Tantangan-tantangan modern seperti sekularisme, relativisme moral, serta perkembangan teknologi dan informasi yang juga mempengaruhi kehidupan umat Kristen. Penelitian ini akan mengulas secara komprehensif berbagai dimensi dalam doktrin Eklesiologi, dimulai dari pengertian dasar Gereja menurut Alkitab, peran Gereja dalam tradisi Kristen, serta perkembangan historis konsep Gereja. Selain itu, akan dibahas pula bagaimana Gereja berperan dalam kehidupan umat beriman melalui sakramen, pewartaan Injil, serta tindakan sosial. Metode yang digunakan dalam penelitian ini yaitu deskriptis studi kepustakaan dengan berbagai sumber seperti buku, jurnal, artikel yang berkaitan dengan doktrin gereja. Adapun hasil temuan peneliti, bahwa doktrin gereja memiliki peran penting terhadap kehidupan umat Kristen. Hal ini berdasarkan, ajaran yang ada pada doktrin gereja menjadi dasar iman umat Kristen.